2012
DOI: 10.1007/s13197-012-0710-3
|View full text |Cite
|
Sign up to set email alerts
|

Technology, applications and modelling of ohmic heating: a review

Abstract: Ohmic heating or Joule heating has immense potential for achieving rapid and uniform heating in foods, providing microbiologically safe and high quality foods. This review discusses the technology behind ohmic heating, the current applications and thermal modeling of the process. The success of ohmic heating depends on the rate of heat generation in the system, the electrical conductivity of the food, electrical field strength, residence time and the method by which the food flows through the system. Ohmic hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
98
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(115 citation statements)
references
References 66 publications
(78 reference statements)
3
98
0
4
Order By: Relevance
“…Recently, improvements were made and it is currently used to blanch, pasteurize and sterilize milk, vegetable products, fruit preparations and meat products [101][102][103][104].…”
Section: Ohmic Heatingmentioning
confidence: 99%
“…Recently, improvements were made and it is currently used to blanch, pasteurize and sterilize milk, vegetable products, fruit preparations and meat products [101][102][103][104].…”
Section: Ohmic Heatingmentioning
confidence: 99%
“…It was also found that ohmically heating the rice bran with 1 M sodium chloride solution and with a current value of 20 A for 3 min gave maximum oil extraction with a minimum Tables 1 and 2. The factors affecting the temperature of bran during ohmic heating are, time of ohmic heating, current, conductivity of the bran and sodium chloride solution (Varghese et al 2012). In this experiment, we kept frequency and voltage constant throughout the experiment, so that there was no effect of frequency and voltage of alternating current in the ohmic heating of the samples.…”
Section: Ohmic Heating As a Pre-treatment In Extractionmentioning
confidence: 99%
“…Ohmic heating has proven advantages over conventional thermal processing and novel thermal alternative technolo gies such as microwave heating, radio frequency heating, and induction heating. Better product quality, shorter heating time, lower capital cost, better energy efficiency, and an environmentally friendly process are the key advantages (21). In the 1990s, the development of a new high-frequency (25 to 30 kHz) power supply, which included a signal with an impulsive waveform (period: 40 ps), a modular design, and full-bore electrodes made of stainless steel or titanium (all of which lowered costs), spawned a " second generation" of ohmic processing equipment, providing improved quality results at reduced expense (15).…”
mentioning
confidence: 99%